Comparative effects of β-cyclodextrin, HP-β-cyclodextrin and SBE7-β-cyclodextrin on the solubility and dissolution of docetaxel via inclusion complexation - Sadaquat, Hadia; Akhtar, Muhammad (Journal of inclusion phenomena and macrocyclic chemistry, 2020)
Cyclodextrins possess the ability to increase the apparent solubility and dissolution rate of poorly water soluble drugs. The objectives of the study were to investigate the effect of β-cyclodextrin, hydroxypropyl-β-cyclodextrin and sulfobutyl ether 7 β-cyclodextrin on solubility and dissolution rate of docetaxel. Four different methods (physical mixture, kneading, freeze drying and solvent evaporation) were employed for inclusion complexation, at varying drug to cyclodextrin ratios 1:1, 1:2 and 1:4. The inclusion complexes of docetaxel with β-cyclodextrin, hydroxypropyl-β-cyclodextrin and sulfobutyl ether 7 β-cyclodextrin at molar ratios 1:1 were characterized by fourier transform infrared spectroscopy (FTIR), X-ray diffractometry (XRD), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and proton nuclear magnetic resonance ( 1 H NMR). The dissolution profiles of inclusion complexes were compared with pure drug. The results revealed formation of inclusion complexes between drug and β-cyclodextrin, hydroxypropyl-β-cyclodextrin and sulfobutyl ether 7 β-cyclodextrin as confirmed by FTIR. 1 H NMR revealed inclusion of drug within cyclodextrin cavity with appearance of proton shifts. Drug crystallinity was reduced with physical mixing and kneading method while amorphous form was attained by freeze drying and solvent evaporation method as revealed by XRD. The DSC and TGA confirmed the formation of inclusion complexes with the absence of melting peak of drug. The effect on solubility and dissolution rate of docetaxel was greater with sulfobutyl ether 7 β-cyclodextrin than hydroxypropyl-β-cyclodextrin and β-cyclodextrin when prepared with similar methods. Drug to cyclodextrin ratio 1:1 was the optimum ratio to increase the solubility and dissolution of docetaxel irrespective of the method. It is concluded that sulfobutyl ether 7 β-cyclodextrin had greater effect on solubility and dissolution rate of docetaxel than β-cyclodextrin and hydroxypropyl-β-cyclodextrin at molar ratios 1:1.